Exploring Organizational Citizenship Behavior to Identify Job Performance Based on Perspectives Organizational and Psychological Empowerment in the Hospitality Sector - Muksalmina, Muksalmina; Hidayatullah, Ferdy; Syahyana, Ahmad; SI, Sari Raudhatul Jannah (Heca Sentra Analitika, 2025)
In an era of global competition and digital transformation, improving human resource performance has become a strategic factor for the hospitality industry, which is highly dependent on service quality. This study aims to analyze the role of organizational citizenship behavior (OCB) in mediating the influence of perceived organizational support and psychological empowerment on the job performance of hospitality employees. A quantitative approach was used, with a survey method targeting star-rated hotel employees in Banda Aceh City, Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the direct and indirect relationships between latent variables. The results showed that perceived organizational support and psychological empowerment had a positive and significant effect on job performance, both directly and through the mediation of OCB. OCB was found to play an important role in strengthening the relationship between psychological factors and job performance, particularly through voluntary behaviors such as helping colleagues, maintaining the organization’s image, and improving service effectiveness. These findings confirm that superior performance in the hospitality industry is not only determined by managerial systems, but also by the psychological and social aspects of employees. In the context of Aceh Province, which has distinctive religious values and social norms, organizational citizenship behavior becomes an important mechanism for building professionalism and work ethics in line with Sharia principles. This study provides practical implications for hotel management to improve organizational support, strengthen psychological empowerment, and create a collaborative work culture oriented toward service quality.